2021
DOI: 10.1016/j.gie.2020.12.032
|View full text |Cite
|
Sign up to set email alerts
|

ASGE guideline on the management of cholangitis

Abstract: This document was reviewed and approved by the Governing Board of the American Society for Gastrointestinal Endoscopy.Cholangitis is a GI emergency requiring prompt recognition and treatment. The purpose of this document from the American Society for Gastrointestinal Endoscopy's (ASGE) Standards of Practice Committee is to provide an evidencebased approach for management of cholangitis. This document addresses the modality of drainage (endoscopic vs percutaneous), timing of intervention (<48 hours vs >48 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 33 publications
2
36
0
1
Order By: Relevance
“…[7] It should be noted that procedure-related bleeding reported in previous studies did not clarify whether only the rst ERCP or all procedures needed to manage the bile stones were included [22][23][24] , and the overall adverse event rates of combined therapy would likely be similar to biliary drainage alone after accounting for adverse events occurring during subsequent procedures to remove bile duct stones. [7] In addition, multiple studies have shown the advantage of one-stage endoscopic combined therapy to AC. For example, a study by Yamamiya et al (2017) showed that the number of ERCP procedures in patients with AC was signi cantly lower in the initial combined therapy than biliary drainage alone [median (IQR): 1 (1-1) vs 2 (2-2), P < 0.001], with no signi cant difference in adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] It should be noted that procedure-related bleeding reported in previous studies did not clarify whether only the rst ERCP or all procedures needed to manage the bile stones were included [22][23][24] , and the overall adverse event rates of combined therapy would likely be similar to biliary drainage alone after accounting for adverse events occurring during subsequent procedures to remove bile duct stones. [7] In addition, multiple studies have shown the advantage of one-stage endoscopic combined therapy to AC. For example, a study by Yamamiya et al (2017) showed that the number of ERCP procedures in patients with AC was signi cantly lower in the initial combined therapy than biliary drainage alone [median (IQR): 1 (1-1) vs 2 (2-2), P < 0.001], with no signi cant difference in adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…All patients received initial supportive treatment immediately after admission according to the management guidelines for cholangitis and the guidelines of the Surviving Sepsis Campaign [4,7,14] , including aggressive hydration, vasopressors, organ support and antibiotics (see Supplementary Note 2 for details), together with close monitoring of vital signs ( e.g. pulse, blood pressure, respiratory rate, urinary output, temperature, and level of consciousness) and clinical laboratory parameters ( e.g.…”
Section: Icu Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute cholangitis (AC) is a life-threatening condition that occurs in the presence of biliary obstruction. Although growing evidence confirms that biliary decompression can dramatically decrease the mortality rates associated with AC, the optimal time for biliary drainage remains controversial[ 1 - 3 ]. Most experts agree that the timeframe for biliary decompression is distinct for different severity grades based on the Tokyo guidelines 2018/2013 (TG18/13), which recommend early biliary drainage for Grade II AC and urgent biliary drainage for Grade III AC; however, the exact timeframe is unclear[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the 2019 European Society of Gastrointestinal Endoscopy guidelines recommend biliary drainage as soon as possible in patients with Grade III AC and within 12 h for patients with septic shock, while within 48–72 h for patients with Grade II AC[ 2 ]. Meanwhile, the 2021 American Society of Gastrointestinal Endoscopy (ASGE) guidelines suggest endoscopic retrograde cholangiopancreatography (ERCP) within 48 h in AC patients, regardless of severity[ 1 ]. Some studies have demonstrated a “the earlier, the better” approach for the management of AC cases[ 5 - 8 ].…”
Section: Introductionmentioning
confidence: 99%